6000 Ton Osterberg Load Test Reduces Foundation Costs For Delaware River Tramway - Aly M. Mohammad (Deep Foundations Institute, 2002)
The Delaware River Tramway will link civic and retail developments in Philadelphia, Pennsylvania and Camden, New Jersey. Twin 300-foot towers will anchor the cables at either side of the river. Four high capacity drilled shafts designed by the Geotechnical Department of DMJM+HARRIS support each of the towers. At the Philadelphia tower, each 6-foot diameter shaft extends 130 feet deep and terminates with a 30-foot rock socket. The shafts are situated within the footprint of an existing relieving platform, which complicates the typical construction sequence. Also, the subsurface conditions at the site provide a unique challenge in both the design and construction of the drilled shafts. During the construction of the four-drilled shafts for the Philadelphia tower, a 6000-ton Osterberg load test was performed on the first shaft to verify design assumption and confirm the shaft capacity. The results of the test were utilized to establish load transfer characteristics and develop foundation design parameters suitable for the site conditions. By doing so the Design Engineer was able to reduce the length of the rock sockets on the remaining production shafts by approximately 5 feet per shaft. As a result, the test provided a significant cost saving to the Owner by eliminating 15 feet of rock drilling from the construction costs. This paper presents a description of the unique design and construction methods adopted for the foundations, also on the Osterberg load test including equipment used, number and locations of strain gages, and interpretation of results. The results and findings presented in this paper could benefit both the design and construction industries because it provides a comparison between geotechnical design assumption and actual field measurements; which has always been a challenge particularly for rock formation.